Ethnomathematics study: The use of modulo concept in Kampung Naga - Umbara, Uba; Prabawanto, Sufyani; Anwar, Agus Saeful (Jurnal Infinity, 2025)
This article discusses the ethnomathematics study of the Kampung Naga community in Tasikmalaya, Indonesia. Ethnomathematics can investigate the application of mathematical notions in these cultural activities. The study explored the forms of ethnomathematics in their ideas and activities in living their daily lives. This study uses an ethnomethodological approach with a realistic ethnographic design to show facts and provide broader meaning. Data were collected from five respondents through in-depth interviews. The study results show that the Kampung Naga community uses the modulo concept to determine the criteria for days that can be used to start various activities, such as building or repairing houses, working, farming, and other social activities. This exploration proves that mathematical concepts are integrated into cultural values ​​in everyday life.